Religious and spiritual struggles, religiousness, and alcohol problems among undergraduates. Issue 3 (3rd July 2019) - Stauner, Nick; Exline, Julie J.; Kusina, Jessica R.; Pargament, Kenneth I.
Abstract: Theoretically, religion/spirituality may protect against alcohol problems or facilitate recovery. However, challenges can arise in religious/spiritual life that may contribute to or complicate alcohol problems. Emerging adults often experience difficult transitions from family environments to independent membership in academic communities straddling the legal drinking age boundary. Among underage undergraduates, we hypothesized that religious/spiritual struggles predict more alcohol problems independently of distress and religiousness, and religiousness independently predicts fewer alcohol problems. Our survey of two U.S. universities (total N = 2525) supported these hypotheses. Structural equation models revealed positive correlations between alcohol problems and all six religious/spiritual struggles (divine, demonic, interpersonal, moral, ultimate meaning, doubt), but only moral struggle predicted alcohol problems moderately and independently of religiousness, distress, gender, and non/white ethnicity. Evidence also emerged for negative correlations between religious/spiritual struggles and drinking as it varies independently of alcohol problems. We recommend that alcoholism counselors address clients' religious/spiritual struggles.